2014
DOI: 10.1097/paf.0000000000000113
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Head Injuries in Children Under the Age of 5 Years in Pretoria

Abstract: The incidence of fatal injuries in children has been reported to be highest amongst children aged 1-4 years. Major causes of head injury include road traffic accidents, falls and intentional or inflicted injury (such as non-accidental injury syndrome). This study reviewed the profile of children (under five years of age) who had been admitted to a large urban medico-legal mortuary (in Pretoria, the capital city of South Africa), after having suffered fatal head injuries. This study was conducted over a 5 year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…However, there were no data in 14 cases whether the deceased was passenger or pedestrian. A review of the literature revealed that a great number of studies reported traffic accident as the most common cause of head trauma-related childhood 3,4,6,[21][22][23][24] whereas similar to our findings, some other studies found traffic accident as the second most common cause of head trauma-related childhood deaths. 7,13,25 Of a total of 67 cases involving traffic accident, 40 (60%) were males and 27 (40%) were females, and victims were mostly in 13-to 36-month-age group with 32 cases (48%), in the present study.…”
Section: Traffic Accidentssupporting
confidence: 92%
See 4 more Smart Citations
“…However, there were no data in 14 cases whether the deceased was passenger or pedestrian. A review of the literature revealed that a great number of studies reported traffic accident as the most common cause of head trauma-related childhood 3,4,6,[21][22][23][24] whereas similar to our findings, some other studies found traffic accident as the second most common cause of head trauma-related childhood deaths. 7,13,25 Of a total of 67 cases involving traffic accident, 40 (60%) were males and 27 (40%) were females, and victims were mostly in 13-to 36-month-age group with 32 cases (48%), in the present study.…”
Section: Traffic Accidentssupporting
confidence: 92%
“…It is expressed that pedestrian deaths are higher in low-middle income countries, whereas passenger deaths are higher in high-level income countries. 6 …”
Section: Traffic Accidentsmentioning
confidence: 97%
See 3 more Smart Citations